Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Sektor Properti Di Indonesia (Periode 2019-2022) - Aprillita, Lisa; Oktavianti, Santi; Haqiqi, Teuku Muhammad; Oktaviyani, Henny; Shalahuddin, Muhammad; Rahmania, Vanesha; Dekas, Rikkie (Universitas Sumatera Selatan, 2024)
The property sector is one of the main source for realizing invesment with the main sources coming from the industrial and housing sectors. The purpose of this study is to analytical the variable ROA, ROE, DER, PER, EPS affect stock price. The analytical method used was panel data regression analysis through eviews 12. In this study, researches used side purposive data collection techniques. Purposive sampling is a sampling technique with certain considerations, with a total population of 35 property companies listed on the Indonesia Stock Exchange For the 2019-2022 period and based on predetermined criteria, a sample of 32 companies from the real estate and property sector was obtained in 2019-2022. The results of the study partially show that the four variables ROA,ROE, DER, EPS, and PER have a positive effect on stock prices is DER Simultaneously the three variables ROA, ROE, EPS and PER affectstock prices.